Multicultural Education in the Cultural Arts Festival at Sahabat Alam Palangka Raya School - Ali Sunarno; Cyndi Hutagalung; Dandi Ansa Faulus; Fitri; I Wayan Wahyu Andriana; Lala Indrawati; Melin; Nor Hapipah; Syukur Setia Zai (Universitas Islam Malang, 2023)
This research is motivate by one fact that cannot be denied for Indonesia, namely a multicultural society. A multicultural society has the potential to become a capital for the nation’s progress, but it does not rule out the possibility that it will become a gap and an opportunity for turmoil to arise, such as social conflict, intolerance, and even division. Providing education in the form of instilling the value of multicultural education from an early age is a form of strategic alternative efforts to suppress and prevent destructive social conflicts. Multicultural education is an attempt to build a person’s mindset to appreaciate diversity within a framework of equality in order to develop social skills. One of the formal education that implements and internalizes multicultural education through special programs in order to realize student’s understanding of the urgency of multicultural education is Sekolah Sahabat Alam. Sekolah Sahabat Alam holds an arts and culture festival at the end of each semester. The cultural festival functions as a concept to provide understanding to students so that they live with mutual respect, appreciation, and tolerance. The problem formulation of this research is how to apply multicultural education in cultural festivals at Sekolah Sahabat Alam in Palangka Raya. This research method was used descriptive research intended to describe the context of multicultural education in the cultural arts festival at Sekolah Sahabat Alam in Palangka Raya. Multicultural education is used as a concrete first step planting good things, this planting can be seen from several activities implemented by Sekolah Sahabat Alam; 1) Cultural festivals as tool for cultural encounters and seeds for seeding multicultural awareness 2) Multicultural education in the creativity of cultural festivals. Keywords: Multicultural Education, Cultural Arts Festival, Sekolah Sahabat Alam